Rising from the ashes: treatments stabilize carbon storage in California’s frequent-fire forests - Yackulic, Ethan; Elias, Micah; Shannon, Joe; Gilbert, Sophie; Koontz, Michael; Plumb, Spencer; Sloggy, Matthew; Duffy, Katharyn (Frontiers in Forests and Global Change, 2025)
The stability of seasonally dry Western mixed-conifer forests is threatened by the history of fire suppression, logging, and now increasing climate-driven aridity. Durable aboveground carbon storage in living trees–a key ecosystem service of these fire-adapted forests–is at risk due to the disruption of natural fire cycles. Restoring the relationship between fire and forest structure is essential for long-term resilience. Fuel and density reduction treatments can help reestablish this balance by reducing fire severity and enhancing forest function.We evaluated the effectiveness of 216 thinning treatments implemented across California’s Central Sierra Nevada mountain range (2015–2023) using a natural experimental design and a novel matching framework. Treatment effects were measured using a dynamic baseline which represents the expected trajectory of a treated site had it remained untreated, accounting for local climate, vegetation, and disturbance conditions. Treatments reduced average fire severity by 32% and the prevalence of high-severity fire by 88%. Larger treatments (>6 ha) were especially effective, seemingly acting as fuel breaks when located near fire perimeters (<250 m). Notably, treated areas continued to sequester and retain carbon during the extreme 2020 drought, while untreated areas declined. Despite intentional biomass removal, carbon levels in nearly 75% of treated forests matched or exceeded baseline levels by year seven, with an average increase of 12.8 ± 4.7 Mg C ha−1.These results highlight the role of treatments in restoring resilient forest structures, reducing fire severity and drought mortality, and effectively stabilizing live carbon pools. This work provides support for landscape-scale management frameworks in fire-adapted forest ecosystems across the western U.S. in a future of intensifying aridity and stochastic fire occurrence.